2022
DOI: 10.3389/fonc.2022.887653
|View full text |Cite
|
Sign up to set email alerts
|

Selective internal radiation therapy of metastatic breast cancer to the liver: A meta-analysis

Abstract: IntroductionThe aim of this study is to conduct a meta-analysis to assess the efficacy of yttrium-90 selective internal radiation therapy (SIRT) in treating patients with breast cancer with hepatic metastasis.MethodPubMed and The Cochrane Library were queried from establishment to January 2021. The following keywords were implemented: “breast”, “yttrium”, and “radioembolization”. The following variables and outcomes were collected: publication year, region, sample size, study design, presence of extrahepatic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Negative predictors of survival reported in this study included the presence of abdominal pain (median OS 12.8 months vs 38.6 months; P < 0.001), the presence of ascites (median OS 1.7 months vs 35.4 months; P = 0.037), and treatment‐related grade ≥ 2 toxicity at 3 months (5.4 months vs 38.6 months; P = 0.017) 45 . Other negative predictors reported in a 2022 meta‐analysis included hepatic tumour burden >25% (median OS 6.8 vs 10.5 months, P < 0.0139) and the presence of extrahepatic metastases (median OS 5.3 vs 15 months, P < 0.0001) 52 …”
Section: Breast Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…Negative predictors of survival reported in this study included the presence of abdominal pain (median OS 12.8 months vs 38.6 months; P < 0.001), the presence of ascites (median OS 1.7 months vs 35.4 months; P = 0.037), and treatment‐related grade ≥ 2 toxicity at 3 months (5.4 months vs 38.6 months; P = 0.017) 45 . Other negative predictors reported in a 2022 meta‐analysis included hepatic tumour burden >25% (median OS 6.8 vs 10.5 months, P < 0.0139) and the presence of extrahepatic metastases (median OS 5.3 vs 15 months, P < 0.0001) 52 …”
Section: Breast Carcinomamentioning
confidence: 99%
“…45 Other negative predictors reported in a 2022 meta-analysis included hepatic tumour burden >25% (median OS 6.8 vs 10.5 months, P < 0.0139) and the presence of extrahepatic metastases (median OS 5.3 vs 15 months, P < 0.0001). 52 A systematic review of multiple liver-directed therapies in BCLM reported pooled median survival from conventional and drug eluting bead TACE (cTACE and DEB-TACE, 362 patients) at 19.6 months and Hepatic Arterial Infusion Chemotherapy (HAIC, 168 patients) at 11.3 months. 51 Whilst the longest OS reported for all arterial therapies was 47 months from a study of 40 patients undergoing doxorubicin DEB-TACE, with no grade ≥ 3 toxicities, it has not been replicated in other published studies.…”
Section: Breast Carcinomamentioning
confidence: 99%